Adaptation of vernacular roof functions in contemporary residential buildings in Kashan, Iran - Nia, Elham Maghsoudi (2014)
Generally, roofs are designed to provide shelters and protect indoor against extreme weather, while, roofs of the vernacular residential buildings (VRB) in Iran served more than the protective function. In comparison to the past, roofs functions of the contemporary residential buildings (CRB) have been neglected in recent years. This study has aimed to explore the roofs functions in the VRB of Iran and identify the factors that have to be considered in considering adaptation of the vernacular roofs functions for the CRB. The mixed-method case study has been selected for this study and the research has focused on Kashan, a historical city with flat and domed roofs in hot and dry climatic condition. After analysing the literature, the study has developed the theoretical proposition including roofs of residential buildings can provide multiple functions including protective, aesthetic, environmental and cultural functions. The study has considered each local master builder and expert as the qualitative unit of analysis, while, each individual who is living in residential building of Kashan has been the quantitative unit of analysis. Data have been obtained through semi-structured interviews with selected local master builders and experts, non-participant observation of selected VRB, and survey of people’s opinions. Validation of proposition has been obtained through using triangulation in qualitative data collection and statistical analysis. The triangulated data sources including interview, non-participant observations of the selected VRB in Kashan, and survey questionnaire have achieved the same results, all supported the roof functions constructs, and confirmed the proposition. Furthermore, the survey results have shown people have preferred the vernacular roofs and tended to adapt the vernacular roof functions for the CRB. However, economy, privacy, safety, thermal comfort, and people culture have to be considered in adapting the vernacular roof functions in the CRB. Therefore, the study has finalized the proposition to roofs of residential buildings can provide multiple functions including protective, environmental, aesthetic and cultural functions in a private and secured context. In conclusion, the study has contributed in merging modern architecture and lifestyle of people with vernacular roof concepts for improving the roof functions in the CRB of Iran and helped to sustain the vernacular concepts of architecture and traditional values of a developing country when following western lifestyle.